Identification of bioactive compounds and ADMET profile of stem bark of Syzygium samarangense and their potential as antibreast cancer and antiinflammatory - Ahmad Misbakhus Sururi, Tukiran Tukiran, Elvira Ratna Aisa, Muhammad Raihan (Journal of Applied Pharmaceutical Science, 2024)
Syzygium samarangense is a potential herbal plant that can be developed in the medical world. Research related to the use of this plant in the medical world has varied, but the stem bark of the plant is rarely developed. This study aimed to identify the chemical constituents of S. samarangense stem bark and its bioactivity as anticancer and anti-inflammatory in silico. The research method started with extracting and identifying bioactive compounds through liquid chromatography mass spectrometry, followed by molecular docking with Human epidermal growth factor receptor-2 receptors (anticancer targets) and COX-2 (anti-inflammatory targets), as well as absorption, distribution, metabolism, excretion, and toxicity (ADMET) pharmacokinetic analysis. The results showed that this plant’s methanol extract contained 60 bioactive compounds with three potential anticancer and anti-inflammatory compounds: kaempferol-7-rhamnoside-4′-glucoside, syzyginin B, and casuarinin. ADMET analysis displayed that they have similar ADMET profiles, with a potential compound as anti-breast cancer and anti-inflammatory, especially syzyginin B. Further research for the compound is needed, such as in vitro and in vivo, to develop its potential.
Keywords: Casuarinin, kaempferol-7-rhamnoside-4-glucoside, syzyginin B, Syzygium samarangense